A study on the laser-assisted ball-end milling of difficult-to-cut materials using a new back-and-forth preheating method. Issue 5 (July 2016) - Kim, Dong-Hyeon; Lee, Choon-Man
Abstract Laser-assisted machining is an effective process to facilitate the material removal processes of difficult-to-cut materials by laser preheating. Machinability of several difficult-to-cut materials, such as Inconel 718, zirconia, and silicon nitride, was studied including a newly developed back-and-forth preheating method used as an enhanced method to heat the workpiece effectively. Experiments were performed according to the inclination angle of the workpiece, for three-dimensional machining using a computed laser power and feed, on a 5-axes machining center with an additional axis for a laser module. The characteristics of the cutting force and surface roughness of the machined workpiece and the wear of the cutting tool were measured and discussed. Decreases in the cutting force and the enhancement of the surface quality were confirmed using the proposed back-and-forth preheating method in laser-assisted milling on Inconel 718, zirconia, and silicon nitride.